(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: color words, semantics of color terms, green colour, colour component, color perception, symbol. The article is devoted to the study of semantic features of colour notion component «green» in English linguaculture. It discusses in detail the symbolic value of the green in English, identifies the main thematic groups of the component «green». Using linguistic methods of analysis and synthesis of factual material with elements of quantification, the article reveals the percentage of frequency in usage of lexeme «green» in the context of the selected object-conceptual spheres. In this study, it is proved that colour component «green» participates in the description of the objects of living/non-living nature, human qualities, as well as civil and political organizations. Green colour is recognized as the seme of colour component «green» and is mostly added by the semes of “freshness, immaturity”, “young, inexperienced”, “security”, “permission / approval.” It is concluded that the green colour in the English linguistic culture plays an important role in human perception of the world, causing to certain associations in various subject-conceptual areas. Specificity of the semantic structure of the component «green» in English is due to socio-ethno-linguistic-cultural features manifested in special national symbols of color.